THE INFLUENCE OF SOCIAL MEDIA MARKETING ON REPURCHASE INTEREST: THE ROLE OF SATISFACTION AS A MEDIATION AND BRAND TRUST AS A MODERATION IN PS STORE PALU - Kurniadi; Ponirin; Syamsul Bahri Dg Parani; Mohammad Zeylo Auriza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine the effect of Social Media Marketing on Repurchase Intention with Satisfaction as a mediating variable and Brand Trust as a moderating variable at PS Store Palu. The study used a quantitative method with a sample of 100 respondents and was analyzed using PLS-SEM. The results showed that Social Media Marketing had a positive and significant effect on Satisfaction, and Satisfaction had a positive effect on Repurchase Intention. Satisfaction was also able to mediate the effect of Social Media Marketing on Repurchase Intention. Meanwhile, Brand Trust was only able to moderate the relationship between Satisfaction and Repurchase Intention.